Antibacterial composite aluminum foil material and preparation method thereof
By using modified adhesives for hot pressing bonding in aluminum foil composite materials, the problem of insufficient antibacterial performance of existing aluminum foil composite materials is solved, and the excellent antibacterial, flame retardant and waterproof properties of the materials are achieved, meeting the improved usage needs .
Patent Information
- Application Number
- CN202411267253.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing aluminum foil composite materials have insufficient antibacterial properties and cannot meet people's needs for improving health and quality of life in recent years.
Modified adhesive is prepared by epoxy ring opening reaction, esterification reaction, quaternization reaction and hydrolysis polymerization reaction. It is used for hot pressing bonding of the substrate layer, aluminum foil layer and protective layer. The modified adhesive is excellent. antibacterial properties and flame retardant properties, and improve the comprehensive performance of composite materials by modifying polyester materials.
The excellent antibacterial properties, tensile strength, peel strength, flame retardant properties and waterproof properties of composite materials are achieved, while maintaining good elongation of break, meeting the needs of users.
Smart Images

Figure SMS_4 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and specifically relates to an antibacterial composite aluminum foil material and a preparation method thereof. Background Art
[0002] Aluminum foil composite material is a new type of material made of aluminum foil and other materials. Its preparation process mainly includes the steps of compounding, molding and surface treatment of aluminum foil and other materials. First, select aluminum foil of appropriate thickness for compounding with other materials. Common materials include polyethylene, polypropylene, polyester film, etc.; then, use the molding process to make the composite material into the required shape, such as coils, sheets, etc.; finally, treat the surface of the composite material to improve the performance of the aluminum foil composite material. Aluminum foil composite materials have the characteristics of light weight, corrosion resistance, good thermal conductivity, etc., and are widely used in packaging, building materials, electronic products and other fields.
[0003] The patent with application number CN201910525979.7 provides a composite material and its preparation method, in which an anti-ultraviolet layer, a fiber fabric layer, an aluminum foil, a polyester film and a vapor phase anti-rust film are stacked and compounded to form a composite material, and a fiber fabric layer coated with an ultraviolet reflective coating on the outer surface is used as an outer protective layer to ensure the flexibility of the material while improving the tear and puncture resistance of the composite material, and improving the light aging resistance of the composite material; and then compounding the aluminum foil and the vapor phase anti-rust film significantly improves the barrier performance and anti-corrosion and anti-rust ability of the composite material. The invention makes the composite material have excellent barrier, anti-ultraviolet and anti-corrosion and anti-rust properties through the synergistic effect of multiple layers of materials, and its preparation process is simple, the production cycle is short, and the quality is easy to control; application Patent No. CN201711055073.0 provides an aluminum foil-based composite packaging material, including a heat-sealing layer from the inside to the outside, a first graphene layer, an aluminum foil layer, a second graphene layer, a first bonding layer, a kraft paper layer, a second bonding layer, a film layer and a printing layer. The aluminum foil-based composite packaging material provided by the invention has good tear resistance, sealing performance, acid and alkali resistance, and the heavy metal precipitation amount is within the food safety range, and can be widely used in the field of food packaging; aluminum foil composite materials are widely used in cigarettes, medicines, household daily necessities and other fields due to their excellent properties. In recent years, people's attention to health and quality of life has been increasing, resulting in the antibacterial properties of existing aluminum foil composite materials being difficult to meet the needs of users. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an antibacterial composite aluminum foil material and a preparation method thereof. The present invention sequentially utilizes epoxy ring-opening reaction, esterification reaction, quaternization reaction, and hydrolysis polymerization reaction to prepare a modified adhesive, which has excellent antibacterial and flame retardant properties, and also exhibits excellent bonding properties when used for hot pressing bonding of a substrate layer, an aluminum foil layer, and a protective layer; the present invention also utilizes the modified adhesive to modify a polyester material, and utilizes the modified polyester material to prepare a protective layer. The multi-layer composite aluminum foil material provided by the present invention has excellent comprehensive performance and can meet the needs of users.
[0005] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0006] An antibacterial composite aluminum foil material comprises a substrate layer, an aluminum foil layer, and a protective layer arranged in sequence from bottom to top, wherein an adhesive layer is arranged between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer, and the adhesive layer adopts a modified adhesive;
[0007] The preparation method of the modified binder is:
[0008] Step S1, adding cyclohexylaminomethyltriethoxysilane and N,N-dimethylacetamide to a reactor, raising the temperature to 70-80° C. under stirring, then adding N,N-dimethylcyclohexylamine and propylethylene oxide in sequence, reacting for 5-8 hours, cooling to room temperature, filtering, removing the solvent, and drying to obtain product 1;
[0009] Step S2, under a nitrogen atmosphere, add the product 1 obtained in step S1 and N,N-dimethylacetamide to the reactor, raise the temperature to 80-90° C. under stirring, then dropwise add di-n-propyl chlorophosphate, complete the dropwise addition within 1-2 hours, continue stirring the reaction for 1-3 hours, cool to room temperature, remove the solvent after filtering, and dry to obtain product 2;
[0010] Step S3, under a nitrogen atmosphere, adding the product 2 obtained in step S2, 2-methyltetrahydrofuran, to a reactor, raising the temperature to 65-75° C. under stirring, then sequentially adding potassium iodide and 1-chloropropane, reacting for 15-20 hours, cooling to room temperature, removing the solvent after filtering, extracting, concentrating, and drying to obtain a modifier;
[0011] Step S4, adding ethyl orthosilicate to anhydrous ethanol under stirring at room temperature, reacting for 5-15 minutes, then adding the modifier obtained in step S3, continuing the reaction for 5-15 minutes, then adding deionized water, adjusting the pH value to 4-5, raising the temperature to 40-50° C., continuing the reaction for 1-2 hours, cooling to room temperature and standing to obtain a modified binder;
[0012] Among them, the synthetic route of the modifier is as follows:
[0013] ;
[0014] ;
[0015] .
[0016] Silica sol is a micro-nano inorganic material with an amorphous structure. It is composed of nano-scale silicon dioxide polymerized into a network structure. The Si-O bond and H2O bond in silica sol form a very special surface active chemical property, which makes silica sol have good bonding properties. There are a large number of active hydroxyl groups (Si-OH) on the surface of silica sol, which can form strong hydrogen bond adsorption. Under certain conditions, silica sol can be firmly bonded with other substances. The SiO2 particles in silica sol have a large specific surface area. At the same time, there are a large number of polar hydroxyl groups on its surface, which are highly hydrophilic. Many particles are linked to each other in chains, and they interact with each other by hydrogen bonds to form a three-dimensional network structure composed of aggregates. Its intermolecular force is strong and the dispersion uniformity is poor, so it is difficult to effectively exert the nano effect of particles. The present invention uses cyclohexylaminomethyltriethoxysilane and propyl oxirane as raw materials, and an epoxy ring-opening reaction occurs under the action of N,N-dimethylcyclohexylamine to obtain product 1; product 1 further undergoes an esterification reaction with di-n-propyl chlorophosphate to obtain product 2; under the action of potassium iodide, product 2 undergoes a quaternization reaction with 1-chloropropane to obtain a modifier; finally, the silica sol, a hydrolysis product of tetraethyl orthosilicate, is modified by the modifier, and a variety of organic groups are introduced on the surface of the silica sol solid particles by hydrolysis and polymerization to obtain a modified binder. The introduction of organic groups improves the dispersibility and compatibility of the binder in the organic polymer system, and improves the antibacterial property, mechanical property, flame retardant property and waterproof property of the composite material.
[0017] In order to obtain a modified binder and perform functional directional modification on it, the molar ratio of cyclohexylaminomethyltriethoxysilane, N,N-dimethylcyclohexylamine, and propyl ethylene oxide in step S1 is 1:0.03-0.05:0.9-1.1, and the mass volume ratio of cyclohexylaminomethyltriethoxysilane and N,N-dimethylacetamide is 0.1-0.2g / mL; the molar ratio of product 1 and di-n-propyl chlorophosphate in step S2 is 1.4:0.8-1.2, and the mass volume ratio of product 1, N,N -The mass volume ratio of dimethylacetamide is 0.17-0.24 g / mL; the molar ratio of the product 2, potassium iodide and 1-chloropropane in step S3 is 1.1:0.1-0.2:0.9-1.1, and the mass volume ratio of the product 2 and 2-methyltetrahydrofuran is 0.08-0.16 g / mL; the volume ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water in step S4 is 40:70-90:15-25, and the mass volume ratio of the modifier and deionized water is 0.3-0.5 g / mL.
[0018] Furthermore, the substrate layer is a polyethylene terephthalate film layer, and the thickness of the substrate layer is 20-40 μm; the thickness of the aluminum foil layer is 5-20 μm; the thickness of the bonding layer between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer is 10-15 μm; the protective layer is a modified polyethylene terephthalate film layer, and the thickness of the protective layer is 40-80 μm. The preparation method of the modified polyethylene terephthalate film is: polyethylene terephthalate and a modified binder are mixed evenly, put into a screw extruder for extrusion, and then blow molded by a blow molding machine, pulled, and rolled, wherein the mass ratio of polyethylene terephthalate to the modified binder is 100:3-5.
[0019] The present invention also provides a method for preparing an antibacterial composite aluminum foil material, comprising the following steps: using a modified adhesive to perform hot pressing bonding on a substrate layer, an aluminum foil layer, and a protective layer in sequence, and naturally curing the resulting material; wherein the hot pressing bonding temperature is 90-110°C, the pressure is 0.1MPa, and the time is 40-60s.
[0020] The present invention has the following beneficial effects:
[0021] The present invention utilizes multi-step chemical reactions to prepare a modified binder, and introduces phosphate, quaternary ammonium salt and siloxane on the surface of silica sol solid particles. The phosphate structure can promote the polymer to form a carbon layer, release PO· free radicals to capture free radicals generated by combustion, form a covering layer to isolate oxygen, and produce flame retardant gas, etc., so that the composite material has good flame retardant properties; the quaternary ammonium salt structure can kill bacteria by destroying cell membranes, inhibiting enzyme activity and destroying nucleic acids, and has a killing effect on a wide spectrum of bacteria, fungi and some viruses, thereby giving the composite material excellent antibacterial properties; the introduction of siloxane can not only form a cross-linked structure during the curing process, enhance the bonding performance and mechanical properties of silica sol, but also penetrate into the microscopic pores of the polymer material to form a complete and tight antibacterial Water film, thereby improving the waterproof performance of the composite material; in addition, the introduction of various organic groups in the modified binder structure can also significantly improve the dispersibility and compatibility of silica sol solid particles in polyester materials, effectively play the reinforcing role of nanoparticles, and the modified binder interacts with the polyester material to form a tighter structure, which significantly improves the mechanical properties of the composite material; the modified binder molecular structure contains both organic groups and inorganic structures. This special composition and molecular structure make it have both the characteristics of organic matter and the functions of inorganic matter, which can give full play to the bonding effect and significantly improve the interlayer peeling strength between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer.
[0022] The composite aluminum foil material provided by the invention has excellent antibacterial property, tensile strength, peel strength, flame retardant property and waterproof property, while maintaining good elongation at break. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application. Aluminum foil was purchased from Gongyi Boyu Aluminum Sales Co., Ltd., alloy grade 1235; polyethylene terephthalate, brand DuPont, USA, grade RE5329. The raw materials used in the following embodiments are all common commercially available products.
[0024] Example 1
[0025] A method for preparing a modified binder comprises the following steps:
[0026] Step S1, adding cyclohexylaminomethyltriethoxysilane and N,N-dimethylacetamide to a reactor, raising the temperature to 75°C under stirring at 180rpm, then adding N,N-dimethylcyclohexylamine and propyl ethylene oxide in sequence, reacting for 6h, cooling to room temperature, filtering, taking the filtrate, distilling under reduced pressure to remove N,N-dimethylacetamide, and vacuum drying at 70°C for 12h to obtain product 1; wherein the molar ratio of cyclohexylaminomethyltriethoxysilane, N,N-dimethylcyclohexylamine, and propyl ethylene oxide is 1:0.04:1, and the mass volume ratio of cyclohexylaminomethyltriethoxysilane to N,N-dimethylacetamide is 0.15g / mL;
[0027] Step S2, under a nitrogen protective atmosphere, adding the product 1 obtained in step S1 and N,N-dimethylacetamide to the reactor, raising the temperature to 85°C under a stirring condition of 180rpm, then dropping di-n-propyl chlorophosphate, completing the dropping within 1.5h, continuing to stir and react for 2h, cooling to room temperature, filtering, taking the filtrate, distilling under reduced pressure to remove N,N-dimethylacetamide, and vacuum drying at 70°C for 12h to obtain product 2; wherein the molar ratio of the product 1 to di-n-propyl chlorophosphate is 1.4:1.0, and the mass volume ratio of the product 1 to N,N-dimethylacetamide is 0.22g / mL;
[0028] Step S3, under a nitrogen protective atmosphere, adding the product 2 obtained in step S2 and 2-methyltetrahydrofuran to the reactor, raising the temperature to 70°C under a stirring condition of 180rpm, then adding potassium iodide and 1-chloropropane in sequence, reacting for 18h, cooling to room temperature, filtering, taking the filtrate, distilling under reduced pressure to remove 2-methyltetrahydrofuran, then adding a mixed solution of N,N-dimethylformamide, deionized water and ether for extraction, taking the organic phase and concentrating it, and vacuum drying it at 40°C for 24h to obtain a modifier; wherein the molar ratio of the product 2, potassium iodide and 1-chloropropane is 1.1:0.15:1.0, the mass volume ratio of the product 2 and 2-methyltetrahydrofuran is 0.12g / mL, and the volume ratio of N,N-dimethylformamide, deionized water and ether is 1:1:2;
[0029] The NMR results of the modifier are: 1 H NMR (300MHz, DMSO-d6) δ 4.07 (t, 4H), 3.80-3.84 (m, 6H), 3.43-3.46 (m, 1H), 2.79 (t, 1H), 2.54-2.57 (m, 2H), 2.34 (t, 2H), 1.58-1.64 (m, 10H), 1.44-1.46 (m, 4H), 1.32-1.35 (m, 4H), 1.21-1.23 (m, 11H), 1.10-1.12 (m, 2H), 0.87-0.90 (m, 12H);
[0030] Step S4, adding tetraethyl orthosilicate to anhydrous ethanol at room temperature and stirring at 160 rpm, reacting for 10 minutes, then adding the modifier obtained in step S3, continuing the reaction for 10 minutes, then adding deionized water, adjusting the pH value to 4-5 with hydrochloric acid (chemically pure), raising the temperature to 45°C, continuing the reaction for 1.5 hours, cooling to room temperature and standing for 24 hours to obtain a modified binder, wherein the average particle size of the solid particles in the modified binder is 82 nm; wherein the volume ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is 40:80:20, and the mass volume ratio of the modifier and deionized water is 0.4 g / mL.
[0031] An antibacterial composite aluminum foil material comprises a substrate layer, an aluminum foil layer, and a protective layer which are arranged in sequence from bottom to top; an adhesive layer is arranged between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer, and the adhesive layer adopts a modified adhesive; the substrate layer is a polyethylene terephthalate film layer, the thickness of the substrate layer is 30 μm, and the polyethylene terephthalate film can be prepared by conventional techniques in the art; the thickness of the aluminum foil layer is 15 μm; the thickness of the adhesive layer between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer is 12 μm; the protective layer is a modified polyethylene terephthalate film layer; The ester film layer has a thickness of 60 μm, and the thickness of the protective layer is 60 μm. The preparation method of the modified polyethylene terephthalate film is: polyethylene terephthalate and the modified binder are evenly mixed, put into a single screw extruder for extrusion, and then blow-molded by a blow molding machine, towed, and rolled to obtain; wherein, the mass ratio of polyethylene terephthalate to the modified binder is 100:4, and the temperature of each section of the single screw extruder is set as: 250°C for preheating section, 330°C for melting section, 360°C for compression section, 280°C for extrusion section, the screw extrusion speed is 8r / min, the blowing ratio is 3, and the towing ratio is 5.
[0032] A method for preparing an antibacterial composite aluminum foil material comprises the following steps: using a modified adhesive to perform hot-press bonding on a substrate layer, an aluminum foil layer, and a protective layer in sequence, and naturally curing the material for 24 hours; wherein the hot-press bonding temperature is 100°C, the pressure is 0.1 MPa, and the time is 50 seconds.
[0033] Example 2
[0034] A method for preparing a modified binder is prepared according to the method described in Example 1, except that: in step S4, the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, and deionized water is 40:90:15, the mass volume ratio of the modifier and deionized water is 0.5 g / mL, and the average particle size of the solid particles in the modified binder is 85 nm.
[0035] An antibacterial composite aluminum foil material comprises a substrate layer, an aluminum foil layer, and a protective layer which are arranged in sequence from bottom to top; an adhesive layer is arranged between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer, and the adhesive layer adopts a modified adhesive; the substrate layer is a polyethylene terephthalate film layer, the thickness of the substrate layer is 20 μm, and the polyethylene terephthalate film can be prepared by conventional techniques in the art; the thickness of the aluminum foil layer is 20 μm; the thickness of the adhesive layer between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer is 10 μm; the protective layer is a modified polyethylene terephthalate. The thickness of the film layer and the protective layer is 70 μm. The preparation method of the modified polyethylene terephthalate film is as follows: polyethylene terephthalate and a modified binder are evenly mixed, put into a single screw extruder for extrusion, and then blow-molded by a blow molding machine, towed, and rolled to obtain the film; wherein, the mass ratio of polyethylene terephthalate to the modified binder is 100:3, and the temperature of each section of the single screw extruder is set as follows: 250°C for preheating section, 330°C for melting section, 360°C for compression section, 280°C for extrusion section, 8r / min for screw extrusion speed, 3 for blowing ratio, and 4.5 for towing ratio.
[0036] A method for preparing an antibacterial composite aluminum foil material comprises the following steps: using a modified adhesive to perform hot pressing bonding on a substrate layer, an aluminum foil layer, and a protective layer in sequence, and naturally curing the material for 24 hours; wherein the hot pressing bonding temperature is 90°C, the pressure is 0.1MPa, and the time is 60s.
[0037] Example 3
[0038] A method for preparing a modified binder is prepared according to the method described in Example 1, except that: in step S4, the volume ratio of tetraethyl orthosilicate, anhydrous ethanol, and deionized water is 40:70:25, the mass volume ratio of the modifier and deionized water is 0.3 g / mL, and the average particle size of the solid particles in the modified binder is 80 nm.
[0039] An antibacterial composite aluminum foil material comprises a substrate layer, an aluminum foil layer, and a protective layer which are arranged in sequence from bottom to top; an adhesive layer is arranged between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer, and the adhesive layer adopts a modified adhesive; the substrate layer is a polyethylene terephthalate film layer, the thickness of the substrate layer is 40 μm, and the polyethylene terephthalate film can be prepared by conventional techniques in the art; the thickness of the aluminum foil layer is 10 μm; the thickness of the adhesive layer between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer is 15 μm; the protective layer is a modified polyethylene terephthalate The thickness of the film layer and the protective layer is 50 μm. The preparation method of the modified polyethylene terephthalate film is as follows: polyethylene terephthalate and a modified binder are evenly mixed, put into a single screw extruder for extrusion, and then blow-molded by a blow molding machine, towed, and rolled to obtain the film; wherein, the mass ratio of polyethylene terephthalate to the modified binder is 100:5, and the temperature of each section of the single screw extruder is set as follows: 250°C for preheating section, 330°C for melting section, 360°C for compression section, 280°C for extrusion section, 8r / min for screw extrusion speed, 3 for blowing ratio, and 5.5 for towing ratio.
[0040] A method for preparing an antibacterial composite aluminum foil material comprises the following steps: using a modified adhesive to sequentially perform hot pressing bonding on a substrate layer, an aluminum foil layer, and a protective layer, and naturally curing the material for 48 hours; wherein the hot pressing bonding temperature is 110° C., the pressure is 0.1 MPa, and the time is 40 seconds.
[0041] Example 4
[0042] A method for preparing a modified binder is prepared according to the method described in Example 1.
[0043] An antibacterial composite aluminum foil material comprises a substrate layer, an aluminum foil layer, and a protective layer which are arranged in sequence from bottom to top; an adhesive layer is arranged between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer, and the adhesive layer adopts a modified adhesive; the substrate layer is a polyethylene terephthalate film layer, the thickness of the substrate layer is 25 μm, and the polyethylene terephthalate film can be prepared by conventional techniques in the art; the thickness of the aluminum foil layer is 15 μm; the thickness of the adhesive layer between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer is 11 μm; the protective layer is a modified polyethylene terephthalate film layer ... aluminum foil layer is 15 μm; the thickness of the aluminum foil layer between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer is 11 μm; the protective layer is a modified polyethylene terephthalate film layer; the thickness of the aluminum foil layer is 15 μm; the thickness of the aluminum foil layer between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer is 11 μm; the protective layer is a modified polyethylene terephthalate film layer; the thickness of the aluminum foil layer The ester film layer has a thickness of 80 μm and the thickness of the protective layer is 80 μm. The preparation method of the modified polyethylene terephthalate film is as follows: polyethylene terephthalate and a modified binder are evenly mixed, put into a single screw extruder for extrusion, and then blow-molded by a blow molding machine, towed, and rolled to obtain the film; wherein the mass ratio of polyethylene terephthalate to the modified binder is 100:4, and the temperature of each section of the single screw extruder is set as follows: 250°C for preheating section, 330°C for melting section, 360°C for compression section, 280°C for extrusion section, the screw extrusion speed is 8 r / min, the blowing ratio is 3, and the towing ratio is 4.
[0044] A method for preparing an antibacterial composite aluminum foil material comprises the following steps: using a modified adhesive to perform hot-press bonding on a substrate layer, an aluminum foil layer, and a protective layer in sequence, and naturally curing the material for 24 hours; wherein the hot-press bonding temperature is 110° C., the pressure is 0.1 MPa, and the time is 40 seconds.
[0045] Comparative Example 1
[0046] A method for preparing a modified binder comprises the following steps: adding tetraethyl orthosilicate to anhydrous ethanol at room temperature and stirring at 160 rpm, reacting for 10 minutes, adding cyclohexylaminomethyltriethoxysilane, continuing the reaction for 10 minutes, adding deionized water, adjusting the pH value to 4-5 with hydrochloric acid (chemically pure), raising the temperature to 45°C, continuing the reaction for 1.5 hours, cooling to room temperature and standing for 24 hours to obtain the modified binder; wherein the volume ratio of tetraethyl orthosilicate, anhydrous ethanol and deionized water is 40:80:20, and the mass volume ratio of cyclohexylaminomethyltriethoxysilane and deionized water is 0.3 g / mL.
[0047] An antibacterial composite aluminum foil material and a preparation method thereof are prepared according to the method described in Example 1.
[0048] Comparative Example 2
[0049] An antibacterial composite aluminum foil material comprises a substrate layer, an aluminum foil layer, and a protective layer which are sequentially arranged from bottom to top; an adhesive layer is arranged between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer, and the adhesive layer is made of silica sol; the substrate layer is a polyethylene terephthalate film layer, and the thickness of the substrate layer is 40 μm. The polyethylene terephthalate film can be prepared by conventional techniques in the art; the thickness of the aluminum foil layer is 25 μm; the thickness of the adhesive layer between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer is 8 μm; the protective layer is a modified polyethylene terephthalate film layer. The modified polyethylene terephthalate film is composed of a polyethylene terephthalate film layer and a protective layer with a thickness of 60 μm. The modified polyethylene terephthalate film is prepared by mixing polyethylene terephthalate and silica sol evenly, putting the mixture into a single screw extruder for extrusion, and then blow molding the mixture through a blow molding machine, pulling the mixture, and winding the mixture. The mass ratio of polyethylene terephthalate to silica sol is 100:3, and the temperature of each section of the single screw extruder is set as follows: 250°C for preheating section, 330°C for melting section, 360°C for compression section, 280°C for extrusion section, 8r / min for screw extrusion speed, 3 for blowing ratio, and 5 for pulling ratio.
[0050] A method for preparing an antibacterial composite aluminum foil material is prepared according to the method described in Example 1, except that the natural curing time is 48 hours.
[0051] The antibacterial composite aluminum foil materials prepared in Examples 1-4 and Comparative Examples 1-2 were subjected to relevant performance tests. The antibacterial performance test was conducted in accordance with GB / T31402-2015 "Test Method for Antibacterial Performance of Plastic Surfaces"; the tensile strength and elongation at break test were conducted by making the composite aluminum foil material into a 20 mm × 5 mm specimen and using a YG004 electronic single fiber strength tester. The test conditions were: tensile speed 10 mm / min, temperature 25 ° C, relative humidity not more than 70%; the peel strength test between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer was conducted in accordance with GB / T The test was carried out in accordance with GB / T 8808-1988 "Peeling test method for soft composite plastic materials", with a sample width of 200 mm and a test speed of 300 mm / min; the limiting oxygen index test was carried out in accordance with GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test"; the waterproof performance test was carried out by making a 20 mm × 20 mm sample of the composite aluminum foil material, soaking it in a water bath at room temperature for 24 hours, taking it out and wiping it dry, and calculating the water absorption rate. The calculation formula is: A = (M-M0) / M0 × 100%, where A is the water absorption rate (%), M is the mass of the sample after wiping off the water (g); M0 is the initial mass of the sample (g); the above tests were carried out three times and the average value was taken. The test results are shown in Table 1. It can be seen from Table 1 that the antibacterial properties, tensile strength, peel strength, limiting oxygen index and water absorption rate of the composite aluminum foil materials prepared in Examples 1-4 are significantly better than those in Comparative Examples 1-2; the limiting oxygen index of the composite aluminum foil materials prepared in Examples 1-4 is higher than 32.8, reaching the LOI≥27 flame retardant ISO material standard.
[0052] Table 1 Test results of related properties of antibacterial composite aluminum foil materials
[0053]
[0054] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.
Claims
1. An antibacterial composite aluminum foil material, characterized in that: It comprises a base material layer, an aluminum foil layer, and a protective layer which are sequentially arranged from bottom to top, and an adhesive layer is arranged between the base material layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer, and the adhesive layer adopts a modified adhesive; The protective layer is a modified polyethylene terephthalate film layer, and the thickness of the protective layer is 40-80 μm. The preparation method of the modified polyethylene terephthalate film is: polyethylene terephthalate and a modified binder are mixed evenly, put into a screw extruder for extrusion, and then blow-molded by a blow molding machine, pulled, and rolled to obtain; The preparation method of the modified binder is: Step S1, add cyclohexylaminomethyltriethoxysilane and N,N-dimethylacetamide to the reactor, raise the temperature to 70-80°C under stirring, then add N,N-dimethylcyclohexylamine and propyl ethylene oxide in sequence, react for 5-8h, cool to room temperature, remove the solvent after filtering, and dry to obtain product 1, the structural formula of product 1 is: ; Step S2, under a nitrogen atmosphere, add the product 1 obtained in step S1 and N,N-dimethylacetamide to the reactor, raise the temperature to 80-90° C. under stirring, then add di-n-propyl chlorophosphate dropwise, complete the addition within 1-2 hours, continue stirring the reaction for 1-3 hours, cool to room temperature, remove the solvent after filtering, and dry to obtain product 2, the structural formula of product 2 is: ; Step S3, under a nitrogen atmosphere, add the product 2 obtained in step S2, 2-methyltetrahydrofuran, to the reactor, raise the temperature to 65-75° C. under stirring, then add potassium iodide and 1-chloropropane in sequence, react for 15-20 hours, cool to room temperature, remove the solvent after filtering, extract, concentrate and dry to obtain a modifier, the structural formula of the modifier is: ; Step S4, under stirring at room temperature, add ethyl orthosilicate to anhydrous ethanol, react for 5-15 minutes, then add the modifier obtained in step S3, continue to react for 5-15 minutes, then add deionized water, adjust the pH value to 4-5, increase the temperature to 40-50°C, continue to react for 1-2 hours, cool to room temperature and let stand to obtain a modified binder.
2. The antibacterial composite aluminum foil material according to claim 1, characterized in that: The molar ratio of cyclohexylaminomethyltriethoxysilane, N,N-dimethylcyclohexylamine and propylethylene oxide in step S1 is 1:0.03-0.05:0.9-1.1, and the mass volume ratio of cyclohexylaminomethyltriethoxysilane and N,N-dimethylacetamide is 0.1-0.2 g / mL.
3. The antibacterial composite aluminum foil material according to claim 1, characterized in that: The molar ratio of the product 1 to di-n-propyl chlorophosphate in step S2 is 1.4:0.8-1.2, and the mass volume ratio of the product 1 to N,N-dimethylacetamide is 0.17-0.24 g / mL.
4. The antibacterial composite aluminum foil material according to claim 1, characterized in that: In step S3, the molar ratio of the product 2, potassium iodide and 1-chloropropane is 1.1:0.1-0.2:0.9-1.1, and the mass volume ratio of the product 2 and 2-methyltetrahydrofuran is 0.08-0.16 g / mL.
5. The antibacterial composite aluminum foil material according to claim 1, characterized in that: In step S4, the volume ratio of ethyl orthosilicate, anhydrous ethanol and deionized water is 40:70-90:15-25, and the mass volume ratio of the modifier and deionized water is 0.3-0.5 g / mL.
6. The antibacterial composite aluminum foil material according to claim 1, characterized in that: The substrate layer is a polyethylene terephthalate film layer, and the thickness of the substrate layer is 20-40 μm; the thickness of the aluminum foil layer is 5-20 μm; the thickness of the adhesive layer between the substrate layer and the aluminum foil layer, and between the aluminum foil layer and the protective layer is 10-15 μm.
7. The antibacterial composite aluminum foil material according to claim 1, characterized in that: The mass ratio of the polyethylene terephthalate to the modified binder is 100:3-5.
8. The method for preparing the antibacterial composite aluminum foil material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The base material layer, the aluminum foil layer and the protective layer are sequentially hot-pressed and bonded by using a modified adhesive and then naturally cured to obtain the product.
9. The method for preparing the antibacterial composite aluminum foil material according to claim 8, characterized in that: The temperature of the thermal compression bonding is 90-110° C., the pressure is 0.1 MPa, and the time is 40-60 seconds.
Citation Information
Patent Citations
An aluminum foil-based composite packaging material and its preparation method
CN107892090B
Composite material and preparation method thereof
CN110126374A
High-flame-retardant organic phosphate fire-proof plate capable of insulating heat and oxygen and suppressing smoke and preparation method thereof
CN102211344A
Antibacterial organic silicone elastomer emulsion, preparation method and application thereof
CN104817847A